MACHINES OF LOVING GRACE. - VOLLMANN, WILLIAM T. (Foreign Policy)
The author reflects on the growth of the U.S. surveillance state and the abuses that he's witnessed as a result of it. He states that he learned as a result of the U.S. Freedom of Information Act that he had been a suspect in the Unabomber case because he'd written the historical novel "Fathers and Crows" concerning 17th-century Iroquois which the Federal Bureau of Investigation file on him claimed was anti-growth and anti-progress and was a later suspect for the 2001 anthrax attacks because he'd been a suspect of the Unabomber case. He mentions his luggage has been searched multiple times, books have had their bindings slit, and foreign letters never arrive. He reflects on problems with erroneous intelligence and errors of understanding and transcription in the intelligence services.